Pemahaman Hadis Relasi pada non-Muslim Perspektif Moderasi Beragama Lukman Hakim Saifuddin - Khoir, Moh. Misbakhul (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
Lukman Hakim Saifuddin's proposal of religious moderation offers a compelling perspective for understanding Hadith on inter-religious relations. This study aims to present an understanding of Hadith regarding relations with non-Muslims through the lens of Lukman Hakim Saifuddin's religious moderation. To achieve this, the research employs Islamic sciences, hermeneutic approaches, and descriptive methods through content analysis. Lukman Hakim Saifuddin advocates for a balanced, inclusive, and adaptive perspective in interpreting Hadith. His approach emphasizes the humanitarian aspect, ensuring that religious understanding and practice uphold the noble values of religion, particularly in maintaining human dignity and public benefit. The findings suggest that, according to Saifuddin’s religious moderation, Hadith on relations with non-Muslims advocate for harmony under normal conditions, reflecting the universality of Islamic teachings. However, in specific situations where injustice and violations of mutual commitments occur, resistance is necessary to uphold justice and mutual commitments. While Lukman Hakim Saifuddin's concept of religious moderation provides a broad framework, it lacks specific epistemological details for understanding religious texts. Therefore, to effectively apply this idea in interpreting religious texts, it is essential to integrate other scientific tools, especially the science of interpretation, to complement and support the overarching concept of religious moderation.